A review on ZnO-based electrical biosensors for cardiac biomarker detection. (7th June 2017) - Shanmugam, Nandhinee R; Muthukumar, Sriram; Prasad, Shalini
Over the past few decades zinc oxide (ZnO)-based thin films and nanostructures have shown unprecedented performance in a wide range of applications. In particular, owing to high isoelectric point, biocompatibility and other multifunctional characteristics, ZnO has extensively been studied as a transduction material for biosensor development. The fascinating properties of ZnO help retain biological activity of the immobilized biomolecule and help in achieving enhanced sensing performance. As a consequence of recent advancements in this multidisciplinary field, diagnostic biosensors are expanding beyond traditional clinical labs to point-of-care and home settings. Label-free electrical detection of biomarkers has been demonstrated using ZnO-sensing platforms. In this review we highlight the characteristics of ZnO that enable realization of its use in development of point-of-care biosensors toward disease diagnosis, in particular cardiovascular diseases. Lay abstract: The goal of this review is to discuss the features of ZnO in enhancing the sensitivity and selectivity of biomarker detection toward the development of point-of-care diagnostic devices. Basic biosensor design features and fabrication of ZnO nanostructures, strategies for surface modifications and its application toward disease diagnosis are discussed.